Save me a seat - Weeks, Sarah; Varadarajan, Gita. (New York : Scholastic Press, 2016)
Ravi has just moved to the United States from India and has always been at the top of his class; Joe has lived in the same town his whole life and has learning problems--but when their lives intersect in the first week of fifth grade they are brought together by a common enemy (the biggest bully in their class) and the need to take control of their lives.
School Library Journal, March 2016.
Library Media Connection starred, August 2016.
Publisher's Weekly, February 2016.
Kirkus Starred, February 2016.
Booklist, April 2016.
Horn Book, October 2016.
Keywords: East Indians -- United States -- Juvenile fiction; Immigrants -- United States -- Juvenile fiction; Adjustment (Psychology) -- Juvenile fiction; Learning disabled children -- Juvenile fiction; Bullying -- Juvenile fiction; Friendship -- Juvenile fiction; Elementary schools -- Juvenile fiction; East Indians -- Fiction; Learning disabilities -- Fiction; Bullies -- Fiction; Friendship -- Fiction; Schools -- Fiction; Learning disabilities -- Fiction; Bullies -- Fiction; School stories; Native Americans -- United States -- Fiction; East Indians -- United States -- Fiction; Bullying -- Fiction